Organizational reality reports from the firing line - Frost, Peter J.; Mitchell, Vance F.; Nord, Walter R. (Addison-Wesley, 1997)
What is organizational life really like? Read Organizational Reality: Reports from the Firing Line, Fourth Edition. Revised to find out. This human experiences reader includes selections drawn from a wide variety of perspectives: organizational behavior theorists, managers, service workers, blue-collar workers, poets, and short-story writers. More emphasis is placed on the concerns of non-managerial employees than the offerings of conventional textbooks.